Deciphering the therapeutic mechanism of topical WS2 nanosheets for the effective therapy of burn injuries. (December 2022) - So, Yoonhee; Yim, DaBin; Son, Wooic; Lee, Hyunji; Lee, Sin; Choi, Chanhee; Yang, Chul-Su; Kim, Jong-Ho
Highlights: Oxidative stress-suppressive 2H-WS2 nanosheets are prepared as a topical antipyrotic exerting the antioxidative, antiapoptotic, and anti-inflammatory activities. The 2H-WS2 antipyrotic promotes up-regulation of innate antioxidant enzymes and antimicrobial peptides, markedly enhancing the intrinsic cellular defense system. The new insight into the therapeutic mechanism of the 2H-WS2 antipyrotic enables satisfactory healing of deep burn wounds in mice. Abstract: Deep burn injuries are complicated traumas accompanying severe oxidative stress and impairment of inherent cellular defense mechanisms against external bacteria. Accordingly, it is required to suppress oxidative stress and support the recovery of intrinsic defense systems in burn wound lesions, but limited topical treatments are clinically available. Herein, antioxidative and anti-inflammatory 2H-WS2 nanosheets are developed as a biocompatible, topical antipyrotic for the treatment of deep burn wounds. The 2H-WS2 nanosheets functionalized with a block copolymer can effectively suppress extrinsic apoptosis, lipid peroxidation, and inflammation in human keratinocytes by scavenging intracellular reactive oxygen species (ROS) and reactive nitrogen species (RNS). Moreover, the 2H-WS2 nanosheets markedly stimulate the up-regulation of innate antioxidant enzymes and antimicrobial peptides in the skin cells, enhancing their intrinsic cellular defense systems. The combined effects of this 2H-WS2 antipyrotic enables a higher efficacy in the deep burn wounds of mice, accelerating re-epithelialization and satisfactory wound healing as compared with commercial silver sulfadiazine (SSD). The therapeutic mechanism of the 2H-WS2 nanosheets for deep burn wounds is proposed herein and found to be distinctly different from that of SSD. The nanotherapeutics of multifunctional 2H-WS2 nanosheets show potential for use in the treatment of other oxidative stress-induced and inflammatory diseases. Graphical abstract: Image, graphical abstract